Automation and Artificial Intelligence - Muhammad Khairul Azhar, Qaisara Aisyah; Muhamad Hanafi, Nurfazilahaini (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
The integration of Automation and Artificial Intelligence (AI) in accounting has significantly transformed the profession, promising increased efficiency, accuracy, and cost savings. However, these advancements also introduce challenges such as job displacement, ethical concerns, educational gaps, cost barriers, and client trust issues. This paper explores the impact of automation and AI on accounting practices, analyzing both the benefits and challenges they present. AI-driven tools enhance fraud detection, data accuracy, compliance, and financial decision-making while streamlining invoice processing. Nevertheless, concerns regarding workforce adaptation, data security, and legal implications must be addressed to ensure responsible implementation. By bridging educational gaps, fostering transparency, and integrating human oversight, accountants can harness AI's potential while maintaining trust and ethical standards. This study contributes to the ongoing discourse on the future of accounting, offering insights into how professionals can navigate AI-driven transformations effectively.